The importance of electrocardiogram in hypothermia: Osborne J-wave - Milanov Zoran (ABC: časopis urgentne medicine, 2015)
INTODUCTION: Osborne J-wave is most often seen in the hypothermic patients, and is also described in hypokalemia, hypercalcemia, intracranial pathology, myocardial ischemia, etc. It occurs due to transmural a voltage gradient between the epicardium and endocardium. ECG in a mild degree of hypothermia (32-35°C) is usually normal. Moderate hypothermia (28-32°C) is associated with J-waves in the inferolateral leads and prolonged PR interval, QRS complex and QTc interval. In severe hypothermia (<28° C) may occur J-waves in all leads except aVR and V1 and frequent ventricular arrhythmias. THE AIM: is to point out diagnostic and prognostic significance Osborne J wave in hypothermia. MATERIALS AND METHODS: used a retrospective analysis of available medical records of the psychiatric patient with hypothermia. CASE REPORT: A woman of 71 years, psychiatric patient, was found on the floor in a somnolent stupor condition, with no signs of fresh injuries. Physical examination showed very cold and pale skin, the contact is established only to rough touch, in short. She was hypotensive, neurological and auscultatory findings was neat. ECG showed sinus bradycardia about 30 / min. with Osborne J waves who looked like as Pardee wave, in all leads except the AVR and V1. PR interval, QRS complex and QT interval was prolonged. She is immediately warmed with blankets, started resuscitation procedures and under continuous ECG monitoring was transported to the Emergency service department (EMD) of the General Hospital in Vrbas. She is admitted to the intensive care unit (ICU), where she soon died. CONCLUSION: Osborne J wave is the most specific ECG sign and its appearance and location can indicate the degree of severity of hypothermia. QRS width and length of the QT interval may indicate the degree of risk of developing malignant ventricular arrhythmias. Psychiatric therapy worsens hypothermia and increases the risk of malignant arrhythmias.